Purinergic Signaling in Spermatogenesis - Mundt, Nadine; Kenzler, Lina; Spehr, Marc (Frontiers in Endocrinology, 2022)
Adenosine triphosphate (ATP) serves as the essential source of cellular energy. Over the last two decades, however, ATP has also attracted increasing interest as an extracellular signal that activates purinergic plasma membrane receptors of the P2 family (1,2). P2 receptors are divided into two types: ATP-gated nonselective cation channels (P2X) and G protein-coupled receptors (P2Y), the latter being activated by a broad range of purine and pyrimidine nucleotides (ATP, ADP, UTP, and UDP, among others) (3,4). Purinergic signaling mechanisms are involved in numerous physiological events and pathophysiological conditions (5). Here, we address the growing body of evidence implicating purinergic signaling in male reproductive system functions. The life-long generation of fertile male germ cells is a highly complex, yet mechanistically poorly understood process. Given the relatively sparse innervation of the testis, spermatogenesis relies on both endocrine control and multi-directional paracrine communication. Therefore, a detailed understanding of such paracrine messengers, including ATP, is crucial to gain mechanistic insight into male reproduction.⁠